Conductive GelMA/PEDOT: PSS Hybrid Hydrogel as a Neural Stem Cell Niche for Treating Cerebral Ischemia-Reperfusion Injury - Zhang, Yilei; Zhang, Meimei; Zhang, Runlin; Liu, Haining; Chen, Hui; Zhang, Xiaofeng; Li, Chen; Zeng, Qing; Chen, Yunhua; Huang, Guozhi (Frontiers in Materials, 2022)
Cerebral ischemia and the subsequent cerebral ischemia-reperfusion (I/R) injury usually result in neuronal impairment with serious disabilities. Although neural stem cell (NSC) transplantation can help with functional recovery after stroke, due to the improper cellular milieu after brain injury, di-rect NSC transplantation will result low cell survival rates and differentiation efficiency into neu-rons. Here a conductive hybrid hydrogel based on gelatin methacryloyl (GelMA) and poly(3,4-ethylenedioxythiophene): poly (styrene sulfonate) (PEDOT:PSS) was created as a NSC niche for the treatment of cerebral I/R injury. GelMA/PEDOT:PSS hybrid hydrogel promoted the development of NSCs into neurons. GelMA/PEDOT:PSS hydrogel along with NSCs could enhance neuronal activity and minimize apoptosis when co-cultured with oxygen-glucose deprivation/reperfusion (OGD/R) neurons. Furthermore, after 7 days of implantation, GelMA/PEDOT:PSS/NSCs on the infarcted brain of rats subjected to reperfusion injury after middle cerebral artery occlusion (MCAO) was ver-ified to attenuate inflammatory responses. These findings show that the conductive Gel-MA/PEDOT:PSS hybrid hydrogel could regulate NSC development and act as promising cell niches for the treatment of cerebral I/R injury.